IMPLEMENTASI KURIKULUM KETERAMPILAN BISNIS DAN MANAJEMEN UNIVERSITAS TARUMANAGARA PADA SISWA SMA KATOLIK 1 RICCI - Gozali, Lina; Robin, Christhoper; Anderssen, Kenneth; Priyanto, Rafeal Jovan; Wirja, Riki Rahardja; Rosita, Dewi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Community Service, also known as PKM, is a medium for Universitas Tarumanagara to give back towards the local community across Indonesia. In this PKM, the team had chosen the topic of